Marketing Strategies in Maintaining IM3 Product Customer Loyalty - Yuda, Mulfi Sandi; Yulianti , Elis (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study analyzed the marketing strategies for maintaining customer loyalty for IM3 Sukabumi products. A qualitative research method was employed, using interview techniques with five participants. The researcher served as the primary instrument for data collection. To ensure the quality of the data, validation and consistency tests of informant statements were carried out using triangulation techniques. Data analysis was conducted through descriptive analysis, which involved reviewing and synthesizing the research findings. IM3's marketing strategy, based on the 4Ps marketing mix, was adopted and further developed by PT. Maju-Maju Jaya Sukabumi. This strategy, including online marketing across various social media platforms and conventional direct marketing, has been highly effective and appealing to customers. As a result, it has proven successful in maintaining and increasing customer loyalty. This research uses a qualitative approach, and triangulation techniques were applied to validate the consistency and accuracy of the informants' statements. The study focuses on a single product from one company. Future research on similar topics should involve a larger sample size or a broader scope, potentially utilizing a quantitative approach, to provide more comparative results.